Cytomegalovirus-Specific CD8+ T-Cells With Different T-Cell Receptor Affinities Segregate T-Cell Phenotypes and Correlate With Chronic Graft-Versus-Host Disease in Patients Post-Hematopoietic Stem Cell Transplantation - Poiret, Thomas; Axelsson-Robertson, Rebecca; Remberger, Mats; Luo, Xiao-Hua; Rao, Martin; Nagchowdhury, Anurupa; Von Landenberg, Anna; Ernberg, Ingemar; Ringden, Olle; Maeurer, Markus (Frontiers in Immunology, 2018)
Virus-specific T-cell responses are crucial to control cytomegalovirus (CMV) infections/reactivation in immunocompromised individuals. Adoptive cellular therapy with CMV-specific T-cells has become a viable treatment option. High-affinity anti-viral cellular immune responses are associated with improved long-term immune protection against CMV infection. To date, the characterization of high-affinity T-cell responses against CMV has not been achieved in blood from patients after allogeneic haematopoietic stem cell transplantation (HSCT). Therefore, the purpose of this study was to describe and analyse the phenotype and clinical impact of different CMV-specific CD8+ cytotoxic T-lymphocytes (CMV-CTL) classes based on their T-cell receptor (TCR) affinity. T-cells isolated from twenty-three patients during the first year following HSCT were tested for the expression of memory markers, programmed cell death 1 (PD-1) as well as TCR affinity, using three different HLA-A*02:01 CMVNLVPMVATV -Pp65 tetramers (wild-type, a245v and q226a mutants). High-affinity CMV-CTL defined by q226a tetramer binding, exhibited a higher frequency in CD8+ T-cells in the first month post-HSCT and exhibited an effector memory phenotype associated with strong PD-1 expression as compared to the medium- and low-affinity CMV-CTLs. High-affinity CMV-CTL were found at higher proportion in patients with chronic graft-versus-host disease (p<0.001). This study provides a first insight into the detailed TCR affinities of CMV-CTL. This may be useful in order to improve current immunotherapy protocols using isolation of viral-specific T-cell populations based on their TCR affinity.